Law Case Defendant’s Communicative Strategy in Court Trial: A Maxim Violation Analysisin Court Trial: A Maxim Violation Analysis - Raden Rizki Dwiputri Ramadhiani; Ruswan Dallyono; Ernie D. A. Imperiani (Passage, 2020)
This study on maxims violation analyzes the interviews of the defendant, Miryam Haryani, in a video of a proceeding entitled, “JPU Cecar Kesaksian Miryam Dalam Sidang Kasus E-KTP”. The research employs a descriptive qualitative method in which the data of the study were in the form of transcripts of the defendant's answers in answering several questions during the trial. By employing Grice’s (1975) theory of Cooperative Principle, the study uses the four principles which are quantity, quality, relation, and manner. The study reveals that of the three maxim rules violated by Miryam, the maxim of relation was committed the most by the defendant. By violating the maxim of relation, it implied that she tried to hold out the truth in her statements. The findings of this study indicate that Miryam used a strategy in covering their statements to achieve a goal.Keywords: Cooperative Principle, Gricean Maxims, Maxims Violation, Pragmatics.